¿Expiration or Prescription? Civil Compensation in Cases of Judgments Arising From Criminal Procedures for Offenses against Public Administration in the Peruvian Legal System - Díaz Castillo, Ingrid (2019)
This paper analyzes the debate that arose in the Peruvian legal system about whether the term that the State has to collect civil compensation in cases of judgments arising from criminal procedures for offenses against public administration is one of expiration or prescription. The difference is not minor because while the prescription period allows for interruptions, the expiration period is not interrupted even when the debtor performs dilatory maneuvers to avoid payment. This last situation is recurrent in the context of the prosecution of the crimes against the public administration, as they sanction state corruption. In this paper, we intend to contribute to the aforementioned debate based on the revision of the figure of civil compensation and its capacity to combat and prevent corruption. Also, the definition, scope and differences between the figures of the expiration and the prescription will be studied to indicate, on the end, that this last institution is the one applicable to the supposed matters of examination.